Dancing in the dark : a cultural history of the Great Depression - Dickstein, Morris (New York : W.W. Norton, 2010)
Dancing in the Dark shows how our worst economic crisis, as it eroded American individualism and punctured the American dream, produced in the 1930s some of the greatest writing, photography, and mass entertainment ever seen in this country.
1. Introduction: Depression culture -- pt. 1. Discovering poverty. 2. The tenement and the world : immigrant lives -- 3. The starvation army -- 4. The country and the city -- 5. Hard times for poets -- 6. Black girls and native sons -- pt. 2. Success and failure. 7. Beyond the American dream -- 8. What price Hollywood? -- 9. The last film of the 1930s, or, Nothing fails like success -- pt. 3. The culture of elegance. 10. Fantasy, elegance, mobility : the dream life of the 1930s -- 11. Class for the masses : elegance democratized -- pt. 4. The search for community. 12. The populist turn : Copland and the popular front -- 13. Who cares? : the world of Porgy and Bess -- 14. The People vs. Frank Capra : populism against itself -- 15. Shakespeare in overalls : an American troubadour -- 16. Gender trouble : exposing the intellectuals -- 17. Conclusion : the work of culture in Depression America.
Originally published: 2009.
Includes bibliographical references (p. [556]-564) and index.
Keywords: Popular culture -- United States -- History -- 20th century; Depressions -- 1929 -- United States; United States -- Civilization -- 1918-1945.; United States -- Intellectual life -- 20th century; United States -- Social life and customs -- 1918-1945.; United States -- History -- 1933-1945.; United States -- History -- 1919-1933.